Influence of SiO2 micro-particles onto microstructure, mechanical properties and wear resistance of uhmwpe based composite under dry sliding friction; Высокие технологии в современной науке и технике (ВТСНТ-2017) - Noppanuch Puangmalee; Narongrit Sonjaitham; Setthawit Saengthip; Noppanan mungnuae; Surachade Solklin; Surat Wannasri (Технологии материалов новых поколений и наноматериалов, 2017)
Заглавие с титульного экрана